2021
DOI: 10.1111/jocn.16175
|View full text |Cite
|
Sign up to set email alerts
|

Communication training programmes for informal caregivers of people living with dementia: A systematic review

Abstract: Registration and protocol-The review is not registered, and no protocol has been prepared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Communication skills training for carers can improve the wellbeing and quality of life of the person living with dementia, and result in positive interactions during the delivery of care (Eggenberger et al, 2013;Morris et al, 2018;Perkins et al, 2022). However, although skills-based interventions may improve carers' knowledge and communication skills, it is not common for communication skills training to include emotional aspects of care and the changing role dynamics within the caring relationship (Morris et al, 2018;Williams et al, 2018).…”
Section: Background and Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Communication skills training for carers can improve the wellbeing and quality of life of the person living with dementia, and result in positive interactions during the delivery of care (Eggenberger et al, 2013;Morris et al, 2018;Perkins et al, 2022). However, although skills-based interventions may improve carers' knowledge and communication skills, it is not common for communication skills training to include emotional aspects of care and the changing role dynamics within the caring relationship (Morris et al, 2018;Williams et al, 2018).…”
Section: Background and Rationalementioning
confidence: 99%
“…The Empowered Conversations (EC) communication training course for carers was developed in response to the gap in service provision identified through reviewing research literature and carrying out scoping exercises and public engagement work (Innes et al, 2022;Morris et al, 2020;Morris et al, 2021). In addition, a further systematic review of communication training programmes identified that interventions were often based only on basic models of communication, lacked postintervention follow up and used a variety of non-standardised outcome measures (Perkins et al, 2022).…”
Section: Background and Rationalementioning
confidence: 99%
“…Furthermore, very few courses for family care partners demonstrate improvements in specific communication outcomes and even when effects were demonstrated these were not consistent across follow‐up points (Morris et al., 2017); however, several interventions demonstrate an impact on broader communication skills (Morris et al., 2017; Nguyen et al., 2018; Perkins et al., 2021). Across reviews care partner communication skills and knowledge were the outcomes that were most significantly improved by communication‐based training interventions for carers of people living with dementia (Eggenberger et al., 2013; Morris et al., 2017; Nguyen et al., 2018; Perkins et al., 2021). A minority of interventions demonstrated improvements in care partner anxiety and depression (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Gitlin et al., 2010; Judge et al., 2010; Livingston et al., 2013). An additional recent review of communication interventions for informal care partners found that none of the studies reviewed had a significant impact on carer stress (Perkins et al., 2021). This review also identified a high‐quality study of a cognitive behavioural therapy communication intervention that improved care partner quality of life (Barnes & Markham, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation